2021
DOI: 10.3233/jad-210236
|View full text |Cite
|
Sign up to set email alerts
|

Taking the A Train? Limited Consistency of Aβ42 and the Aβ42/40 Ratio in the AT(N) Classification

Abstract: The consistency of cerebrospinal fluid amyloid-β (Aβ)42/40 ratio and Aβ 42 has not been assessed in the AT(N) classification system. We analyzed the classification changes of the dichotomized amyloid status (A+/A–) in 363 patients tested for Alzheimer’s disease biomarkers after Aβ 42 was superseded by the Aβ 42/40 ratio. The consistency of Aβ 42 and the Aβ 42/40 ratio was very low. Notably, the proportions of “false” A+T–patients were considerable (74–91%) and corresponded mostly to patients not clinically dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In line with this, a French memory clinic study reported mostly normal Aβ42/40 levels in A+T− patients and abnormal levels in A−T+ patients. 47 These results support using Aβ42/40 in clinical practice as a CSF marker of A. Aβ42/40 could be particularly informative when Aβ42 and other markers are discrepant. 46,48 Because widely accepted biomarker cutoffs do not yet exist, the normal/abnormal dichotomy in the ATN system is a challenge.…”
Section: Discussionsupporting
confidence: 67%
“…In line with this, a French memory clinic study reported mostly normal Aβ42/40 levels in A+T− patients and abnormal levels in A−T+ patients. 47 These results support using Aβ42/40 in clinical practice as a CSF marker of A. Aβ42/40 could be particularly informative when Aβ42 and other markers are discrepant. 46,48 Because widely accepted biomarker cutoffs do not yet exist, the normal/abnormal dichotomy in the ATN system is a challenge.…”
Section: Discussionsupporting
confidence: 67%
“…However, the Aβ 42 /Aβ 40 ratio was abnormally reduced in both, allowing the diagnosis of AD. Despite some concerns about the interchangeability between Aβ 42 and the Aβ 42 /Aβ 40 ratio in the AT(N) system [64], the ratio shows better diagnostic accuracy compared to Aβ 42 alone [32,65], correlates better with amyloid imaging by positron emission tomography [32], and its better diagnostic performance has been confirmed in pathologically proven cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid AD biomarker values were collected as previously described ( 8 ) and measured using either ELISA (INNOTEST) or the Lumipulse G1200 system (Fujeribo, Ghent, Belgium) in line with the manufacturer’s procedures. For samples quantified by ELISA, abnormal values were defined as amyloid-β 42 (Aβ 42 ) <500 pg./mL or Aβ 42/40 ratio ≤ 0.05, phosphorylated-tau >60 pg./mL, total-tau >450 pg./mL, according to the cutoff values recommended by the manufacturer, internal data and in the literature ( 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cerebrospinal fluid AD biomarker values were collected as previously described ( 8 ) and measured using either ELISA (INNOTEST) or the Lumipulse G1200 system (Fujeribo, Ghent, Belgium) in line with the manufacturer’s procedures. For samples quantified by ELISA, abnormal values were defined as amyloid-β 42 (Aβ 42 ) <500 pg./mL or Aβ 42/40 ratio ≤ 0.05, phosphorylated-tau >60 pg./mL, total-tau >450 pg./mL, according to the cutoff values recommended by the manufacturer, internal data and in the literature ( 8 , 9 ). For samples quantified with Lumipulse, abnormal values were defined as Aβ 42 ≤ 600 pg./mL, or Aβ 42/40 ratio ≤ 0.07, phosphorylated-tau >60 pg./mL, total-tau >450 pg./mL, according to the cutoff values recommended by the manufacturer, and internal data.…”
Section: Methodsmentioning
confidence: 99%